RUSSIA'S STRATEGIC INTERESTS IN THE AREA OF SECURITY OF ENERGY SUPPLY - O. B. Lomakina (Модернизация, инновация, развитие, 2017)
The modern world with linked and interpenetrating processes more and more often raises pressing issues of security and stability. However, in the past the term "security" was used in a broad strategic sense of the word (for example when describing country's border safety or territorial integrity, etc.), nowadays this term is infl uenced by economic factors such as an important issue of security of energy supply. This issue should not be underestimated, even though it does not seem to play an important role in the country's security. The oil crises of the late 20th and the early 21st centuries have proved how much the global economy depends on the price of energy resources, an increase in which might provoke a dramatic recession not only in any given country but throughout the world.The traditional view holds that Russia could not be aff ected or infl uenced by any energy issues, since it has some of the richest energy resources in the world, hence the rising issues of security of energy supply were mostly neglected. However, the last few years have revealed the fl aws and shortsightedness of this approach. Irregularities in energy supply, the increasing shortages of natural gas and problems related to its transit to Europe are the first signs of forthcoming problems. If these problems are persistently ignored, it might lead to a full-scale energy crisis within the next few years. All of the above highlights the relevancy of the present article.The purpose of this article is to determine Russia's strategic interests in the area of global security of energy supply.With this in view the following objectives have been accomplished: The term of "security of energy supply" was defined in relation to the Russian Federation; Russia's energy policy was examined and analyzed; Priority tasks and objectives for Russia in the field of security of energy supply were defined.